Gefangen in Kanada: Zur Internierung deutscher Handelsschiffsbesatzungen während des Zweiten Weltkriegs - Kestler, Judith (transcript, 2017)
Captivity as a transnational space of possibility – this volume impressively shows why numerous German sailors wanted to emigrate to Canada after 1945.